2013
DOI: 10.18632/oncotarget.974
|View full text |Cite
|
Sign up to set email alerts
|

P53 Mutations in Advanced Cancers: Clinical Characteristics, Outcomes, and Correlation between Progression-Free Survival and Bevacizumab-Containing Therapy

Abstract: ABSTRACT:Background: Mutations in the p53 gene are amongst the most frequent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

9
1

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 40 publications
(35 reference statements)
9
88
0
1
Order By: Relevance
“…We found that 96% of our patients demonstrated at least one molecular alteration, and 85% had two or more alterations. The most frequent alteration was TP53 mutation, found in 44% of our patients, similar to previous reports (16).…”
Section: Discussionsupporting
confidence: 92%
“…We found that 96% of our patients demonstrated at least one molecular alteration, and 85% had two or more alterations. The most frequent alteration was TP53 mutation, found in 44% of our patients, similar to previous reports (16).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, patients with TP53 mutations exhibited a higher rate of clinical benefit with VEGF/R inhibitors, a finding observed in our previous work (27). Possible explanations include a role of TP53 mutations in promoting vascularization.…”
Section: Discussionsupporting
confidence: 56%
“…Kara and colleagues (15) examined only 34 patients and analyzed p53 expression, not mutational status; Ince and colleagues (16) examined survival, not PFS. In contrast, the multivariate analysis demonstrating that a bevacizumab-containing regimen was an independent factor associated with better outcomes in TP53-mutated patients included a variety of tumors and analyzed PFS (5).…”
Section: Resultsmentioning
confidence: 99%